THE EFFORT OF SUNDAY SCHOOL TEACHERS TO LOVE AND EDUCATE CHILDREN TO FULFIL THE GOD’S DESIGN THROUGH THEIR PERSONALITY - Yosefo Gule (INNOVATIO: Journal for Religious Innovations Studies, 2022)
The author investigated the efforts of Sunday school teachers to love and educate children to fulfil God's design through their personalities. The research method was a descriptive qualitative study with a library research approach. The lack of understanding of a Sunday school teacher on students' personality, character, and temperament was one aspect that triggers why Sunday school teachers did not love and educate children wholeheartedly. Therefore, it is essential for Sunday school teachers to love and educate children to fulfil God's design through their personalities. Loving and educating children aims to reach their maximum potential for Jesus in the context of the gifts and qualities that God has abundantly bestowed upon each child. Sunday school teachers need to educate children to attain higher levels of spiritual excellence in pious, wise and knowledgeable and learned personalities. The purpose of studying the personality of Sunday school children is to understand, reach, and teach students more effectively through the unique personality that God has given to students so that we can bring honour and glory to God. Abstrak: Penulis menginvestigasi upaya guru sekolah minggu mengasihi dan mendidik anak-anak untuk memenuhi rancangan Allah melalui kepribadiannya. Metode penelitian pada penulisan artikel ini adalah menggunakan metode kajian kualitatif deskriptif dengan pendekatan library research. Kurangnya pemahaman seorang guru sekolah minggu terhadap kepribadian, karakter, dan tempramen peserta didik, merupakan salah satu aspek yang memicu mengapa guru sekolah minggu kurang mengasihi dan mendidik anak-anak dengan sepenuh hati. Oleh sebab itu sangat penting peranan guru sekolah minggu untuk mengasihi dan mendidik anak-anak untuk memenuhi rancangan Allah lewat kepribadiannya. Mengasihi dan mendidik anak-anak bertujuan untuk mencapai potensi mereka secara maksimal bagi Yesus dan melakukan hal ini dalam konteks karunia dan kualitas yang telah dikaruniakan Tuhan secara limpah kepada masing-masing anak. Guru sekolah minggu perlu mendidik anak-anak untuk mencapai level keunggulan rohani yang lebih tinggi dalam kepribadian yang saleh, bijaksana dan berpengetahuan serta terpelajar. Tujuan mempelajari kepribadian anak-anak sekolah minggu adalah untuk memahami, menjangkau, dan mengajar murid-murid secara lebih efektif melalui kepribadian khususnya yang diberikan Allah kepada anak didik, sehingga kita bisa mendatangkan kehormatan dan kemuliaan bagi Allah. Kata-kata kunci: guru sekolah minggu, kepribadian, mengasihi, mendidik